Thermal stability and mechanical properties of HVOF/PVD duplex ceramic coatings produced by HVOF and cathodic vacuum arc. Issue 10 (July 2017) - Chen, Wanglin; Fang, Bo; Zhang, Daoda; Meng, Xianna; Zhang, Shihong
Abstract: Duplex ceramic coatings, consisting of an inner NiCr-Cr3 C2 -based coating and an outmost AlCrN film, were produced on the steel substrate in succession by velocity oxygen-fuel spraying (HVOF) and cathodic vacuum arc methods, and then isochronally annealed at annealing temperatures below 900 °C for 2 h. The thermal stability and mechanical properties of the annealed samples were systematically studied by means of X-ray diffraction, Optical microscope and transmission electron microscope, in association with mechanical property measurements. The results show that the microstructure, phase evolution and mechanical properties of duplex ceramic coatings are significantly dependent on the annealing temperature. Metastable fcc-AlCrN solid solution in AlCrN film first decomposes to rich-Al and rich-Cr domains by spinodal decomposition at 700 °C, leading to a notable increase in hardness due to its smaller grain size and high elastic strain field, and then to equiaxed hcp-AlN and Cr2 N by the nucleation and growth at 900 °C, leading to a notable decrease in hardness due to the recrystallization and the formation of hcp-AlN. Meanwhile, the both decarburization of Cr3 C2 to Cr7 C3 occurs at 800 °C, but becomes more intensive at 900 °C, leading to a notable loss in hardness. In addition, the dissolution of Cr3 C2 produces high density of porosity, which also reduces the hardness. The hardness tests show the following ordering of load-bearing capacity for the duplex ceramic coatings: 700 °C>As-deposited >800 °C>900 °C. Tribological property measurements demonstrate that the wear resistance of the tested duplex ceramic coatings obeys the following ordering: 700 °C>As-deposited >800 °C>900 °C. The improved wear resistance is due to high surface hardness, load-bearing capacity and thermal stability. In addition, the wear mechanisms are shown.